Prediksi Perubahan Penggunaan Lahan di DAS Deli Hulu Menggunakan Metode Artificial Neural Network - Harahap, Ahmad Husein; Satia Negara Lubis; Bejo Slamet (Jurnal Serambi Engineering, 2025)
Human demand for land continues to increase with rapid population growth. This rapid population growth rate will certainly affect land cover changes, which will be increasingly high and may have an impact on land and environmental conversion, especially in the river basin area. One of the catchments that may be affected is the Deli catchment, in particular the Deli Hulu catchment area. The Deli Hulu watershed is geographically located in the administrative area of Deli Serdang Regency and Karo Regency, which have large populations. Therefore, this triggers land use patterns. This study aims to analyse the changes of land cover in Deli Hulu Watershed area in 2013, 2018, 2023 to predict the land cover in 2033. This study uses 6 driving factors, namely distance from roads, distance from rivers, distance from settlements, population density, slope and altitude. This study uses Artificial Neural Network-Markov chain modelling to predict land cover changes in 2033. The results of the study show that the predicted land cover in the Deli Hulu watershed in 2033 is Dryland Forest 3,318 ha (17.16%), Plantations 2,800 ha (14.48%), Settlements 959 ha (4.96%), Dryland Agriculture 11,311 ha (58.49%), Rice Fields 873 ha (4.51%) and Open Land 78 ha (0.40%).